The characteristics of 'gap-year' students and their tertiary academic outcomes - Birch, E.; Miller, Paul (Wiley-Blackwell Publishing Asia, 2007)
This study examines the determinants of taking a ‘gap-year’ (the decision to take a year off study between completing high school and commencing university) and the subsequent impact of this decision on marks at university. It finds that the main factors influencing students’ decisions on university deferment are their previous academic achievements, age and location. Students who defer university are found to have higher marks than students who commence university directly after completing high school. This mark advantage is more pronounced among low-performing students, particularly male students, who are in the lower-half of the university marks distribution.